E EFEKTIVITAS TINDAKAN PENAGIHAN PAJAK DENGAN SURAT TEGURAN, SURAT PAKSA, SPMP DALAM MENCAPAI TARGET PENERIMAAN PAJAK DI KANTOR PELAYANAN PAJAK (KPP) PRATAMA MEDAN POLONIA - Herti Diana Hutapea (Fakultas Ekonomi dan Bisnis, Universitas HKBP Nommensen, 2020)
The purpose of this study to determine the level of effectiveness of warning letters, compulsory letters, SPMP and the contribution of tax arrears disbursement at the Kantor Pelayanan Pajak (KPP) Pratama Medan Polonia. The data used in this research is secondary data. Secondary data were obtained from direct research objects, namely KPP Pratama Medan Polonia, Tax Billing Section and other references relevant to this research. The analytical method used in this research is a comparative descriptive analysis to provide an overview of whether tax collection with a warning letter, warrant, SPMP is effective or not, and how much contribution is given to the total income tax revenue. The data analysis technique used is descriptive ratio analysis. The test results show that tax collection with Warning Letter, Forced Warrant, SPMP 2017-2018 is classified as ineffective and contributes very less to income tax revenue. Therefore, it is better if KPP Pratama Medan Polonia needs to provide counseling about taxation to the general public and taxpayers in particular so that they understand, are aware and want to carry out their tax obligations properly.